Benefits and limitations of human resource accounting / Che Kartina Idrus - Che Kartina, Idrus (Faculty of Accountancy, 1992)
Human Resource Accounting ( HRA ) is. a new approach in evaluating human resources that represents the current status of human resources valuation concept; which currently is being developed mostly in the Western countries. By helping management'identify and evaluate the human resources attributes that can make the firm more profitable, human resources planning can also make a significant contribution to a business. There is a difficulty of measuring Human Resources, therefore an audit firm has been chosen as a field of study since it keep tracks of amount of hours spent on each of the audit staff.